2005
DOI: 10.1038/sj.gt.3302646
|View full text |Cite
|
Sign up to set email alerts
|

A combination of DNA vaccines targeting human papillomavirus type 16 E6 and E7 generates potent antitumor effects

Abstract: Human papillomavirus (HPV) infects large numbers of women worldwide and is present in more than 99% of all cervical cancers. HPV E6 and E7 are two viral oncoproteins that are consistently expressed in HPV infections and HPVassociated malignancies. We have previously developed DNA vaccines encoding calreticulin (CRT) linked either to HPV type 16 (HPV-16) E6 or to HPV-16 E7, both of which generated significant antitumor effects against E6-and E7-expressing tumors. In this study, we demonstrate that simultaneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 25 publications
2
46
0
Order By: Relevance
“…For instance, since E6 and E7 are both important for the malignant transformation of HPV-associated neoplasia and are coexpressed in nearly all HPV-associated tumors, both antigens represent ideal candidates for codon optimization. We have previously demonstrated that coadministration of CRT/E6 and CRT/E7 vaccines generates a better anti-tumor effect compared to the administration of either CRT/E6 DNA or CRT/E7 DNA [25]. In view of this observation, it is likely that a combination of DNA vaccines encoding codon-optimized E6 and codon-optimized E7 may provide more potent antitumor effects than vaccination with codon-optimized E6 alone.…”
Section: Discussionmentioning
confidence: 95%
“…For instance, since E6 and E7 are both important for the malignant transformation of HPV-associated neoplasia and are coexpressed in nearly all HPV-associated tumors, both antigens represent ideal candidates for codon optimization. We have previously demonstrated that coadministration of CRT/E6 and CRT/E7 vaccines generates a better anti-tumor effect compared to the administration of either CRT/E6 DNA or CRT/E7 DNA [25]. In view of this observation, it is likely that a combination of DNA vaccines encoding codon-optimized E6 and codon-optimized E7 may provide more potent antitumor effects than vaccination with codon-optimized E6 alone.…”
Section: Discussionmentioning
confidence: 95%
“…We have demonstrated that mice vaccinated with CRT/E6 DNA generated significant E6-specific CD8 + T-cell immune responses and could protect vaccinated mice from challenge with E6-expressing TC-1 tumors compared to vaccination with wild-type E6 DNA. 6,7 Thus, DNA vaccines encoding CRT are capable of significantly enhancing the DNA vaccine potency.…”
Section: Introductionmentioning
confidence: 99%
“…In a preclinical study with SFV replicon particles we also demonstrated higher anti-tumor immunity with the inclusion of both E6 and E7 compared to either oncogene alone. 43 Furthermore, in patients with HPV neoplasia both E6 and E7-specific CD8 + T cell responses have been correlated with better prognostic value. 44 Despite the lower immunogenicity observed with the variant of E7, administration of either a 0.2 or 0.05 ug dose of E7sh resulted in a significant delay in tumor growth compared to the control group.…”
Section: Discussionmentioning
confidence: 99%